PROMOTING KARO CULTURE AND TRADITION BY DESIGNING JAMBUR AND TRADITIONAL MARKET AS A COMMUNITY CENTER IN BUKIT LAWANG, NORTH SUMATERA, INDONESIA - S, Nicholas Jonanda; Ginting , Salmina Wati (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Jambur and traditional markets are buildings that are often used by the Karo community. Jambur is used as a place to organize Karo cultural events such as marriage ceremonies, death (simate-mate), and others. The market is used as a place to conduct buying and selling activities. Nowadays, many markets also function as jambur. The community functions several kiosks or stalls in a row into a jambur, also known as jambur los. This is because existing jambur tend to be expensive, exclusive and only available in a few locations in big cities. This is less than the number of Karo people who still use jambur for all traditional activities. The unification of the jambur function within the traditional market has both positive and negative sides. The positive side of this unification is the availability of a multi-functional community center that is easy and cheap. In addition, this community center can function as a cultural expression and tourism promotion. The negative side is the problem of congestion and chaos due to market activities that tend to be dirty and crowded. This paper examines the design of a jambur within a traditional market in Gotong Royong Village, Bukit Lawang, North Sumatra. In addition to functioning as a community center, the design is also expected to promote Karo culture and the Bukit Lawang tourist destination. The method chosen was descriptive qualitative method and literature study where the author collected literature data about Karo culture, directly observed the environmental conditions of the object and interviewed residents of Gotong Royong Village. The design is expected to solve the problem of congestion and market chaos while supporting the expression of Karo culture and promoting the Bukit Lawang tourist destination.